Geotechnical characteristics of saline soft soils improved by chemical agents - Fattah Mohammed (Magazine of Civil Engineering)
Chemical stabilization is a typical method for enhancing salinity in soils. In this regard, an effort has been made to evaluate the effect of chemical substances and stabilizers of Portland cement on the geotechnical characteristics of salt soils. Due to their geologic makeup, textural characteristics, and climatic factors, the majority of the soils in the southern part of Iraq are notable for having a wide variety of formations. Because the soil particles in the saline regions of Thi-Qar governorate are encircled by molecules of chlorides, sulfates, or other salt species that function as link agents to fill in the gaps in the dry state, these soils may generally be categorized as saline soils. The sort of salt in such soil determines how it should be disposed of. The objective of this study is to investigate the effect of adding different types of salt compounds including NaCl, MgCl2, Na2SiO3, and CaCl2 with various percentages 2, 4, 8, and 10 % and Portland cement for improving the consistency limits and shear strength of saline soft soils. It was found that adding cement materials and a group of chlorides NaCl, MgCl2, Na2SiO3, and CaCl2 increased the unconfined compressive strength of the soil from 290 to 814, 506, 404, 574, and 422 kPa, respectively, and decrease the consistency limits.